Piriformospora indica Reprograms Gene Expression in Arabidopsis Phosphate Metabolism Mutants But Does Not Compensate for Phosphate Limitation - Bakshi, Madhunita; Sherameti, Irena; Meichsner, Doreen; Thürich, Johannes; Varma, Ajit; Johri, Atul K.; Yeh, Kai-Wun; Oelmüller, Ralf (Frontiers in Microbiology, 2017)
Piriformospora indica is an endophytic fungus of Sebacinaceae which colonizes the roots of many plant species and confers benefits to the hosts. We demonstrate that approximately 75% of the genes which respond to P. indica in Arabidopsis roots differ among seedlings grown on normal phosphate (Pi) or Pi limitation conditions, and among wild-type and the wrky6 mutant impaired in the regulation of the Pi metabolism. Mapman analyses suggest that the fungus activates different signaling, transport, metabolic and developmental programs in wild-type and wrky6 roots under normal and low Pi conditions. Under low Pi, P. indica promotes growth and Pi uptake of wild-type seedlings, and the stimulatory effects are identical for mutants impaired in the PHOSPHATE TRANSPORTERS1;1, -1;2 and -1;4. The data suggest that the fungus does not stimulate Pi uptake, but adapts the expression profiles to Pi limitation in Pi metabolism mutants.